2024
DOI: 10.1101/2024.05.22.595372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tango-seq: overlaying transcriptomics on connectomics to identify neurons downstream ofDrosophilaclock neurons

Alison Ehrlich,
Angelina A. Xu,
Sofia Luminari
et al.

Abstract: Knowing how neural circuits change with neuronal plasticity and differ between individuals is important to fully understand behavior. Connectomes are typically assembled using electron microscopy, but this is low throughput and impractical for analyzing plasticity or mutations. Here, we modified the trans-Tango genetic circuit-tracing technique to identify neurons synaptically downstream of Drosophila s-LNv clock neurons, which show 24hr plasticity rhythms. s-LNv target neurons were labeled specifically in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…To our knowledge, this is the first demonstration that a pair of G2Ns are broadly tuned to both bitter and sweet gustatory inputs while also integrating metabolic information (Figure 8A). trans-Tango and its variants have been successfully used to study connectivity and functionality in various neuronal circuits, including gustatory, olfactory, visual systems, mushroom body output neurons or clock neurons 24,[58][59][60][61] . Recent analysis of the retro-TANGO tool, showed that a minimum number of synaptic connections between neurons is needed to label the postsynaptic neurons properly.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first demonstration that a pair of G2Ns are broadly tuned to both bitter and sweet gustatory inputs while also integrating metabolic information (Figure 8A). trans-Tango and its variants have been successfully used to study connectivity and functionality in various neuronal circuits, including gustatory, olfactory, visual systems, mushroom body output neurons or clock neurons 24,[58][59][60][61] . Recent analysis of the retro-TANGO tool, showed that a minimum number of synaptic connections between neurons is needed to label the postsynaptic neurons properly.…”
Section: Discussionmentioning
confidence: 99%